Pendidikan dan Kekuasaan dalam Lintas Peradaban: Kajian Pustaka - Liana Miftakhul Jannah; Serli Meilinda; Eko Prastyo; Syarif Hidayatullah; Noval Pabriyansah; Afriantoni Afriantoni (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
This article aims to analyze the dialectical relationship between education and power throughout the history of civilizations, and to explain the strategic role of education as an agent of social transformation. This research employs a literature study method (library research) by examining various academic literatures, books, and relevant scientific journals. The findings indicate that in ancient civilizations, education was elitist and designed to maintain existing power hierarchies. In Islamic civilization, education played a dual role: as a center for scientific advancement supported by rulers, and simultaneously as a tool for political legitimation. During the colonial era, education functioned as a mechanism for social control, yet paradoxically fostered nationalist consciousness among the oppressed. In the modern era, education has become a crucial state policy instrument, while simultaneously possessing the potential to critically challenge oppressive power structures. In conclusion, education inherently possesses a dual function as both a tool for power reproduction and a vehicle for social change. Therefore, educational management must be conducted inclusively, fairly, and democratically to truly empower society and build a more just and advanced civilization.